In silico Identification of Novel Compounds as Quorum-Sensing Inhibitors in Selected Waterborne Pathogens - Bawar, Khirsten Marie; Cruz, Leannie Praise; Ilao, Kristine Bernadette; Justiniano, Julianne Mica; Panganiban, Lara Mae; Fabito, Diane Laine; Amayun, Christine Joy; Nas, John Sylvester (Asian Journal of Biological and Life Sciences)
Quorum sensing (QS) is a process involved in producing, detecting, responding, and releasing signaling molecules to maintain physiological activities of most utilized by both gram-positive and gram-negative bacteria in various environmental conditions. This study aims to identify novel compounds that have potential QS inhibitory mechanisms against the gram-positive bacteria Staphylococcus aureus (S. aureus) and Streptococcus pneumoniae (S. pneumoniae), and the gram-negative bacteria Salmonella typhi (S. typhi) and Escherichia coli (E. coli). Compounds that are structurally similar to the known QS inhibitors were identified using ligand-based screening. Candidate compounds with 40 to 80% similarity with the known QS inhibitors were further evaluated through molecular docking with the QS-associated enzymes, namely ComA, ComE, LsrF, LsrK, AgrC, AgrA, LsrB, and Hfq. The binding affinity was visualized to identify the different non-covalent binding interactions. Compounds with <-8.0 kcal/mol docking score were considered for evaluation for their distribution coefficient (LogD) at different optimal growth of the bacteria, such as pH 4, 6, 7.4, 7.8, 8, and 9. Out of the 63 compounds evaluated, only three compounds demonstrated a high binding affinity, namely 1-phenyl-3-[5-(phenylcarbamoylamino)naphthalen-1-yl]urea and 1-naphthalen- 1-yl-3-[5-(naphthalen-1-ylcarbamoylamino)naphthalen-1-yl]urea with ComE of S. pneumoniae and 3-[(4-Methylphenyl)sulfonyl][1,2,3]triazolo[1,5-a]quinazolin-5(4H)-one to AgrA of S. aureus. Their high binding affinity may be attributed to the numerous hydrogen bonds and hydrophobic interactions. However, only 3-[(4-Methylphenyl)sulfonyl][1,2,3]triazolo[1,5-a]quinazolin-5(4H)-one has comparable LogD value with its QS inhibitor of AgrA, savarin, at the optimal growth pH for S. aureus. These findings suggest that the use of 3-[(4-Methylphenyl)sulfonyl][1,2,3]triazolo[1,5-a] quinazolin-5(4H)-one may be effective in controlling S. aureus growth probably through inhibition of AgrA. However, further studies are needed to confirm these findings.
Keywords: in silico; Ligand-based screening; Molecular docking; Quorum sensing; Waterborne pathogens